Pengaruh Literasi dan Inklusi Keuangan Syariah Terhadap Kinerja Keuangan UMKM di Surabaya - Alfarisy, Fathor Rozy; Canggih, Clarashinta (Universitas Negeri Surabaya, 2025)
In Indonesia, Mikro, Small, and Medium Enterprises (MSMEs) are one of the important pillars in Indonesia’s economic development where they make a large contribution to the country’s economy. In the dynamics of the global economy, the resilience and stability of the country’s economy not only depends on the size of the corporate sector, but also on the strength of the MSMEs sector, which is an important foundation. The present study employs a quantitative associative research method, with multiple linear regression analysis used as the data analysis technique. The findings indicate that financial literacy and Islamic financial inclusion have a significant effect on the financial performance of MSMEs in Surabaya. The results further demonstrate that Islamic financial literacy and inclusion contribute directly to the improvement of MSMEs’ financial performance. Therefore, the strengthening of education and access to Islamic financial services needs to be continuously enhanced